2017
DOI: 10.18103/mra.v5i3.1121
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of lifestyle risk factors in employees: A quasi-experimental study in Sousse, Tunisia

Abstract: Background:A better understanding of the prevalence and clustering patterns of multiple lifestyle-related health factors may support efforts to handle efficiently chronic diseases, reduce their incidence and improve overall health outcomes. This study aimed to evaluate the effectiveness of a three-year based intervention in the workplace on clustering of non-communicable diseases' risk factors. Methods:We based our study on a quasi-experimental intervention study (pre and post assessments with intervention and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Studies indicate that programs focused on health promotion intervention and awareness on multiple risk factors, such as smoking, physical activity and diet simultaneously, are more effective in reducing chronic NCD. (13,14) It is believed that people with clustering of risk factors can be motivated and sensitized more quickly, so that they are more responsive to intervention programs. (13) The low consumption of fruit, the second most prevalent factor, may be related to the high cost it represents, especially when considering low-income populations, or even because they are being neglected, given the wide availability of fast foods and processed products.…”
Section: ❚ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies indicate that programs focused on health promotion intervention and awareness on multiple risk factors, such as smoking, physical activity and diet simultaneously, are more effective in reducing chronic NCD. (13,14) It is believed that people with clustering of risk factors can be motivated and sensitized more quickly, so that they are more responsive to intervention programs. (13) The low consumption of fruit, the second most prevalent factor, may be related to the high cost it represents, especially when considering low-income populations, or even because they are being neglected, given the wide availability of fast foods and processed products.…”
Section: ❚ Discussionmentioning
confidence: 99%
“…(13,14) It is believed that people with clustering of risk factors can be motivated and sensitized more quickly, so that they are more responsive to intervention programs. (13) The low consumption of fruit, the second most prevalent factor, may be related to the high cost it represents, especially when considering low-income populations, or even because they are being neglected, given the wide availability of fast foods and processed products. (27) A study evaluating markers of food consumption found, with the greater purchasing power through the Bolsa Família Program, there was an increase in the consumption of foods considered unhealthy.…”
Section: ❚ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os fatores de risco para as Doenças Crônicas Não-Transmissíveis (DCNT) estão relacionados aos hábitos de vida, entre eles se destacam a obesidade, o sedentarismo, a dieta inadequada e o tabagismo 11 . Apesar do papel de cada um desses fatores de risco estar bem estabelecido, a aglomeração deles, além de ocorrer sistematicamente, é agravante e favorece um pior prognóstico, considerando o efeito multiplicativo da associação 12,13 . É relevante destacar que a simultaneidade ou aglomeração desses fatores é relativamente comum, considerando a grande interrelação entre eles.…”
Section: Introductionunclassified